USING SYSTEMIC APPROACH TO IMPROVE STUDENTS’ ADJECTIVE MASTERY AT SEVENTH GRADE STUDENTS OF SMP NEGERI 21 MAKASSAR - Wahyuni, Ika Yuli; Akil, Mansur; Talib, Ahmad; Sangkala, Ismail (Fakultas Keguruan dan Ilmu Pendidikan, 2018)
This research aimed at finding out whether or not systemic approach can improve students’ adjective mastery. Pre-experimental design was applied in this research with one group pretest - posttest design. The population of this research was the seventh grade students of SMP Negeri 21 Makassar, academic year 2017/2018, which consisted of 8 classes. This research used simple random sampling. The samples were 26 students of 7A. The research instrument used vocabulary test consisted of word form, word meaning, and word use as the research instrument. The result of this research showed that the application of systemic approach can improve students’ adjective mastery. The result of this research showed that the application of systemic approach can improve students’ adjective mastery. It was proved by the t-test value which was lower than 0.05. it was (0.00) > (0.05) and degree of freedom (n-1) = 25. And the result of the result showed that the mean score of pre-test was 54.64 and mean score of post-test was 78.16.